Identitas Dalam Mata Kuliah Bahasa Indonesia di Jurusan Teknik Kelautan 2019 Institut Teknologi Sepuluh Nopember Surabaya - Encik Savira Isnah (SULUK: Jurnal Bahasa, Sastra, dan Budaya, 2020)
This study aims to determine the identity that emerges through language in Indonesian language major in tertiary engineering concentration. The research was conducted in the Department of Marine Engineering, Sepuluh November Institute of Technology Surabaya. The method used is descriptive qualitative with Van Dijk's critical discourse analysis. Van Dijk's three models are macrostructure, social cognition, and microstructure. The results of the study show that identity does not only emerge from a person's psychological background but is also seen from the language used. most students try to use mimicry in using language, that is, students outside Surabaya try to use Suroboyoan as the language of instruction in discussions in the Indonesian class as an effort to bring out their identity as suroboyo architects, no longer their origin areas to be socially acceptable. Other findings, Indonesian language classes bring up the identity associated with the understanding adopted by students.